Konstrukcja "odsetkowej" ulgi mieszkaniowej w podatku dochodowym od osób fizycznych a wspieranie przez państwo indywidualnych inwestycji budowlano-mieszkaniowych (ocena polskich i czeskich rozwiązań) - Kurková, Karina (Construction of "Interest" Housing Allowances in the Income Tax on Natural Persons vs. Supporting Individual Building-Housing Investments by the State (Evaluation of Polish and Czech Solutions), 2005)
The present article aims at bringing closer one of the forms of supporting the development of the individual housing building industry by the state, which are the allowances in the income tax on natural persons. Because of the use of the article, the author concentrates on the newest regulations limiting the study to the "interest" housing allowance functioning in Poland since 2002. In order to value and criticize this institution, for comparison there were presented the solutions in this field used in the Czech Republic - the country so similar to Poland as regards economic and social position. Through the analysis of the construction of interest allowance, the author tries to answer the question if such an allowance constitutes the encouragement to embark on own building-housing investment and who is going to benefit from its sophisticated form.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 39-50